Applying Ligninolytic Fungi on Eucalyptus grandis Wood for Pulping Pretreatment or Fractionation - Inalbon, María Cristina (2015)
The effects of three different fungal treatments on several technology characteristics of Eucalyptus grandis wood, were studied on industrial chips and blocks. The percentage of the substrate mass loss by the fungal treatment, and the relative amount of extractives and lignin were determined. The effective capillarity of wood, pH and total reducing sugars concentration in water-soluble fraction (WSF) were also determined. There was a reduced mass loss of the substrate by the fungal treatment (less than 3%). Gelatoporia subvermispora FBCC 313 showed the highestreduction in the Klason lignin content, the highestendoglucanase activity on the WSF as well asthe highest ability to increase the effectively capillarity in the radial wood direction. This last effect is interesting since it might facilitate the wood impregnation processes and therefore to reduce the consumption of reagents in industrial treatments.